Disorders of Sex Development in a Large Ukrainian Cohort: Clinical Diversity and Genetic Findings - Globa, Evgenia; Zelinska, Natalia; Shcherbak, Yulia; Bignon-Topalovic, Joelle; Bashamboo, Anu; MсElreavey, Ken (Frontiers in Endocrinology, 2022)
Abstract Background The clinical profile and genetics of Disorders/Differences of Sex Development (DSD) has not been reported in Ukraine. Materials and methods We established the Ukrainian DSD Register and identified 682 DSD patients. This cohort includes, 357 patients (52.3% (303 patients with Turner syndrome)) with sex chromosome DSD, 119 (17.4%) with 46,XY DSD and 206 (30.2%) with 46,XX DSD. Patients with sex chromosome DSD and congenital adrenal hyperplasia (CAH, n=185) were excluded from further studies. Fluorescence in situ hybridization (FISH) was performed for eight 46,XX boys. 79 patients underwent Whole Exome Sequencing (WES). Results The majority of patients with 46,XY and 46,XX DSD (n=140), were raised as female (56.3% and 61.9% respectively). WES (n=79) identified pathogenic (P) or likely pathogenic (LP) variants in 43% of the cohort. P/LP variants were identified in the androgen receptor (AR) and NR5A1 genes (20.2%). Variants in other DSD genes including AMHR2, HSD17B3, MYRF, ANOS1, FGFR11, WT1, DHX37, SRD5A1, GATA4, TBCE, CACNA1A and GLI2 were identified in 22.8% of cases. 82.3% of all P/LP variants are novel. 35.3% of patients with a genetic diagnosis had an atypical clinical presentation. Known pathogenic variants in WDR11, a gene known to cause congenital hypogonadotropic hypogonadism (CHH), were identified in individuals with primary hypogonadism. Conclusions WES is a powerful tool to identify novel causal variants in patients with DSD, including a significant minority that have an atypical clinical presentation. Our data suggest that variants in the WDR11 gene are unlikely to be a cause of CHH.